Species variation and spatial differences in mucin expression from corneal epithelial cells. (November 2016) - Leonard, Brian C.; Yañez-Soto, Bernardo; Raghunathan, Vijay Krishna; Abbott, Nicholas L.; Murphy, Christopher J.
Abstract: Mucins are large glycoproteins expressed by epithelial cells of both the conjunctiva and cornea, and principle components of the glycocalyx. They are thought to play an important role in determining the interactions between the cornea/conjunctiva and the overlying tear film. The purpose of this study was to characterize the membrane-associated corneal mucin expression pattern from multiple species commonly used in ophthalmic research and drug development to better define the biochemical attributes of the ocular surface. Humans, rhesus macaques and dogs were found to have a very similar pattern of mucin expression, with mucin 16 (MUC16) being the most prevalent mucin transcript. In contrast, the rabbit had a unique mucin expression pattern with all mucin transcripts expressed at relatively similar levels. To determine if there were spatial differences in expression, peripheral and central corneal epithelium were individually isolated and evaluated for mucin expression. In all species examined, MUC1, MUC4 and MUC16 had higher peripheral corneal expression when compared with central, which reached statistical significance in MUC1 (rhesus and dog). The data demonstrated variation in corneal epithelial membrane-associated mucin expression between species, with the rabbit having a distinct expression pattern. These differences may be reflective of the environment, pathogen exposure or tear film dynamics of the respective species. The species differences, as well as regional mucin expression patterns, characterized in this study further define the biochemical composition of the ocular surface and may play an important role in tear film stability. Highlights: Rabbits have a unique pattern of corneal epithelial mucin expression compared with humans, rhesus macaques and dogs. Peripheral cornea tends to have higher mucin expression when compared with central cornea. Species variation and spatial mucin expression should be evaluated as determinants of tear film stability.